Covid-19: food insecurity, digital exclusion and Catholic schools - McKinney, Stephen J. (Journal of Religious Education, 2020)
Covid-19 and the subsequent worldwide lockdowns have had a major impact on families and school education. The lockdowns have highlighted and exacerbated the disadvantages experienced by those children who suffer from child poverty. This article focuses on food insecurity and the digital divide, or digital exclusion, and argues that these have emerged as very pressing issues during lockdowns for children suffering from child poverty. The article provides an outline of the response of the Catholic Church and Catholic schools, primarily in the United Kingdom. There have been some concerted efforts to address food insecurity by providing food and food vouchers for children and vulnerable families. It has proved more problematic to address digital exclusion and the article argues that for those children who experience digital exclusion, this can effectively mean exclusion from the religious education, religious life, community and the pastoral and spiritual support that is normally offered by the Catholic school.